MicroRNA-33 regulates the synaptic plasticity-related gene ARC in temporal lobe epilepsy - Yuchen Xu; Lily Zhang; Yan Yan; Wenbiao Xiao; Wei Zou; Zhaohui Luo; Bo Xiao; Hongyu Long (Neuroscience Research)
This study aimed to elucidate the expression patterns of miR-33 and ARC in both a rat model of temporal lobe epilepsy (TLE) and human TLE patients, to explore the role of miR-33 in epilepsy onset through its regulation of ARC expression in the hippocampus. Our findings, supported by a Dual-Luciferase reporter assay, suggest that miR-33 can bind to the 3′ UTR region of ARC. We observed that miR-33 levels were reduced at 1 hour and 60 days post-seizure, while ARC expression notably increased at these time points. In the hippocampal CA1 and CA3 regions of post-seizure rats, ARC expression significantly exceeded that of control groups. Following the transfection of HEK cells with a miR-33 mimic, there was a decrease in both ARC mRNA and protein levels, whereas the group treated with a miR-33 inhibitor displayed the opposite effect. RNA sequencing in TLE patients revealed a similar miR-33 and ARC interaction. The regulation of Arc expression by miR-33 suggests that Arc may be a target gene of miR-33 in the context of epilepsy. Our findings indicate that miR-33 downregulation could contribute to the dysregulation of Arc expression observed in TLE, potentially influencing the disease process. Further studies are required to establish the exact role of miR-33-mediated Arc regulation in the development of epilepsy.